2021
DOI: 10.9734/arjass/2021/v13i330214
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partners Violence in Sub-Saharan Africa: Review of Risk Factors and Impacts

Abstract: Background: Intimate Partner Violence (IPV) against women is one of the most known public health concerns. The depth of the problem varies across regions and different settings. The purpose of this scooping review is to assess the overall prevalence and risk factors of IPV in the context of Sub-Saharan Africa (SSA). Methods: The review was conducted based on 24 articles selected from PubMed and google search. The selection considered only those conducted in SSA based on a representative sample size of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…We found that 71.6% of women who had no access to water and 72% of women who had no access to a toilet reported a form of IPV. These findings align with a multi-country survey in SSA on IPV as reported by Guli and Geda [ 18 ] that has consistently highlighted the high prevalence of IPV in slums associated with lack of water and sanitation facilities. However, to achieve the objectives of this study, we controlled for other covariates to analyse the association between WASH accessibility and IPV exposure.…”
Section: Discussionsupporting
confidence: 90%
“…We found that 71.6% of women who had no access to water and 72% of women who had no access to a toilet reported a form of IPV. These findings align with a multi-country survey in SSA on IPV as reported by Guli and Geda [ 18 ] that has consistently highlighted the high prevalence of IPV in slums associated with lack of water and sanitation facilities. However, to achieve the objectives of this study, we controlled for other covariates to analyse the association between WASH accessibility and IPV exposure.…”
Section: Discussionsupporting
confidence: 90%
“…43,44 Similar to other studies, depression, alcohol abuse, and number of previous pregnancies were associated to IPV prevalence. 73,74 While additional research focusing on the links between ACEs, IPV, depression, and alcohol abuse outcomes among pregnant/breastfeeding women living with HIV in this setting is warranted, the evidence from this study suggests that those experiencing forms of IPV and ACEs also have concomitant conditions such depression and alcohol abuse.…”
Section: Discussionmentioning
confidence: 88%
“…The trends of experience of the various forms of IPV, with emotional violence being the most common, are similar to what has been reported in South Africa, where 81% of pregnant women who experience IPV reported emotional abuse, 76% reported physical abuse and 26% reported sexual abuse. 26 Emotional and physical violence have been identified as common forms of IPV in countries in SSA, 17,27 and sexual violence appears to be under-reported in several African settings because of the stigma associated with IPV victims. 17 The prevalence of women's exposure to interparental violence in this study is similar to the prevalence reported in some developing countries, such as Bangladesh (26.4%), 18 but significantly higher than the prevalence reported in many developed countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The trends of experience of the various forms of IPV, with emotional violence being the most common, are similar to what has been reported in South Africa, where 81% of pregnant women who experience IPV reported emotional abuse, 76% reported physical abuse and 26% reported sexual abuse. 26 Emotional and physical violence have been identified as common forms of IPV in countries in SSA, 17 , 27 and sexual violence appears to be under-reported in several African settings because of the stigma associated with IPV victims. 17 …”
Section: Discussionmentioning
confidence: 99%